Disseminated nocardiosis after unrelated bone marrow transplantation. Issue 6 (10th November 2016) - Hino, Yutaro; Doki, Noriko; Senoo, Yasushi; Sekiya, Noritaka; Kurosawa, Shuhei; Tsuboi, Satoshi; Ohashi, Kazuteru
Abstract: Nocardiosis is a rare bacterial infection occurring mainly in patients with deficient cell‐mediated immunity. Although disseminated nocardiosis after allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is a rare complication, it is associated with high mortality. Moreover, after allo‐HSCT, nocardiosis may be mistaken for other bacterial or fungal infections because clinical and radiographic findings of pulmonary, cerebral, and cutaneous nocardiosis lesions are non‐specific. Here, we report a case of disseminated nocardiosis (caused by Nocardia abscessus ) with skin, pulmonary, liver, lymph node, and multiple brain abscesses in a patient after allo‐HSCT. The patient initially responded clinically and radiographically to imipenem/cilastin and trimethoprim‐sulfamethoxazole therapy. Clinicians should be aware of the possibility of nocardiosis in allo‐HSCT recipients who are treated with multiple immunosuppressive agents to control chronic graft‐versus‐host disease. Accurate diagnosis and identification of disseminated nocardiosis is important to ensure administration of the correct antibiotic regimen.